Shortened G1 phase of cell cycle and decreased histone H3K27 methylation are associated with AKT‐induced enhancement of primordial germ cell reprogramming. (14th June 2019) - Takehara, Asuka; Matsui, Yasuhisa
Abstract: Primordial germ cells (PGCs) are reprogrammed into pluripotent embryonic germ cells (EGCs) under specific culture conditions, but the detailed mechanisms of PGC reprogramming have not yet been fully clarified. Previous studies have demonstrated that AKT, an important intracellular signaling molecule, promotes reprogramming of PGCs into EGCs. Because AKT likely inhibits p53 functions to enhance PGC reprogramming, and p53 negatively regulates cell cycle progression, we analyzed cell cycle changes in PGCs following AKT activation and found that the ratio of PGCs in the G1/G0 phase was decreased while that of PGCs in the G2/M phase was increased after AKT activation. We also showed that the expression of the CDK inhibitor p27 kip1, which prevents the G1‐S transition and is transcriptionally repressed by p53, was significantly downregulated by AKT activation. The results suggested that the characteristic cell cycle changes of PGCs by AKT activation are, at least in part, due to decreased expression of p27 kip1 . We also investigated changes in histone H3K27 tri‐methylation (H3K27me3) by AKT activation in PGCs, because we previously found that decreased H3K27me3 was involved in PGC reprogramming via upregulation of cyclin D1. We observed that AKT activation in PGCs resulted in H3K27 hypomethylation. In addition, DZNeP, an inhibitor of the H3K27 trimethyl transferase Ezh2, stimulated EGC formation. These results together suggested that AKT activation promotes G1‐S transition and downregulates H3K27me3 to enhance PGC reprogramming. Abstract : We show here that enhancement of primordial germ cell (PGC) reprogramming into pluripotent stem cells by AKT activation is associated with shortened G1 phase via downregulation of a negative cell cycle regulator p27 and decreased histone H3K27 tri‐methylation. Our results shed light on downstream events of AKT activation resulting in acceleration of cellular reprogramming.